Catalogue of the Byzantine coins in the Dumbarton Oaks Collection and in the Whittemore Collection. Vol. III : Leo III to Nicephorus III, 717-1081. Pt. 1 : Leo III to Michael III, 717-867. - Grierson, Philip. (Washington)
ix, 470 s., 29 s. res.